Simulation and analysis of the secondary-particle-induced background of the follow-up x-ray telescope onboard Einstein Probe - Zirui Situ; Jingbin Lu; Yanji Yang; Haodi Wang; Ruopu Li; Qingyang Li; Yong Chen; Yupeng Xu (AIP Advances, 2022)
The Einstein Probe (EP) is a small scientific satellite committed to time-domain astronomy and high-energy astrophysics. One of the main payloads in the EP is the Follow-up X-ray Telescope (FXT). To get a quantity of in-orbit data as a reference, data from the Insight-Hard X-ray Modulation Telescope (Insight-HXMT) were adopted. The Insight-HXMT is dedicated to perform hard x-ray all-sky surveys, which has a parallel in-orbit environment with the EP. In this paper, we simulated the in-orbit background of an FXT by the Particle and Heavy-Ion Transport code System, which is the first general-purpose heavy ion transport Monte Carlo code, which has a simulated range from 0.01 meV to 1 TeV. The influence from protons in the EP orbital environment and the secondary rays caused by the shielding materials around the detector have been mainly considered. The Super Monte Carlo Simulation Program for nuclear and radiation Processes has been used to define the materials of the shielding structure. An isotropic source of protons and a complete shielding structure have been constructed in this simulation. First, the spectrum of background between 0.5 and 15 keV has been calculated. Second, we simulated the types of reactions and the fluxes of secondary particles, and all of them were calculated with the same model in the first step. Finally, we considered the effectiveness of the outermost shielding with different materials. Among the calculated spectra of background, we found two conspicuous energy responses with high counts, separately located in 7.345 keV (5 eV) and 8.045 keV (5 eV). Compared with the in-orbit data from the low energy x-ray telescope in the Insight-HXMT, the simulated results are credible. Considering the combination of the simulated types of reactions and fluxes of secondary particles, we could mostly judge that the secondary photons brought the photoelectric effects, which caused the two conspicuous responses in the spectrum of background. In addition, copper was the most suitable material for the outermost shielding in this simulation.